Adapted Physical Education in Brazilian Public Schools: A Systematic Review Towards Pupils with Special Educational Needs - Barros, Denyse Leonor Modesto; Coelho, Carly de Faria; Martins, Patrícia Sardinha Leonardo Lopes (Fronteira: Journal of Social, Technological and Environmental Science, 2023)
Adapted Physical Education (APE) in Brazilian public schools: a systematic review towards children with Special Educational Needs. The main purpose of this review was to verify empirical studies on adapted physical education for all students with special educational needs (SEN) in Brazilian public schools over the past 15 years, hence proposing future research guidelines. A systematic procedure for searching the literature was used to, which covered a total of 28 research-based papers from computerized Scopus database. Mixed methods inquiries were employed in the reviewed studies. The publication descriptor data were quantitatively examined via VOSviewer software (van Eck & Waltman, 2010), while applying the content perspective on the descriptive data to assist the trustworthiness and credibility of the analysis. Results demonstrated that except for Haegele et al (2017)/Meletti & Ribeiro (2104) among the studies, deficiencies exist in past literature relative to the adapted physical education in Brazilian public schools. In practical terms this highlights that the voice of children with special educational needs have not been heard yet in the official literature. Future research might need to consider, despite the mostly favorable consensus about inclusion subject, teachers’ feelings, their supports, and resources to effectively conceive adapted physical education programs.